Regulatory framework for polymer-based nanotherapeutics in clinical translation - Stucchi, Federico; Li, Min; Castellano, Giuseppe; Cellesi, Francesco (Frontiers in Bioengineering and Biotechnology, 2026)
Polymer-based nanotherapeutics (PNs) have emerged as versatile drug delivery platforms offering controlled release, targeted delivery, and improved pharmacokinetics across therapeutic areas. However, their structural complexity and nanoscale behavior pose significant regulatory challenges. Current frameworks still evaluate PNs under conventional pharmaceutical and biological regulations, overlooking nanospecific properties and leading to case-by-case assessments. This review examines critical quality attributes, analytical requirements, and gaps in standardization that hinder clinical translation. Key issues include inadequate characterization of the physicochemical properties, scalability of manufacturing, and limited predictability of in vivo performance. Highlighting the mismatch between nanoscale properties and existing regulatory expectations, this review underscores the need for a harmonized, science-driven framework to ensure safety, efficacy, and global acceptance of PNs.